INFORMASI DAN TEKNOLOGI DALAM PERSPEKTIF PENDIDIKAN ISLAM - Suriadi adi Samsuri (Al-Mau'izhoh, 2022)
The presence of educational technology is a necessity to overcome the problems of education in remote-lagging regions. Although initially only expected to be able to "reach" those left and behind as a consequence of the strategy of expanding and equitable access to education, but did not rule out in its development able to be a supporter of quality improvement and competitiveness. Ideally, the use of educational technology should not only cease the ability to "reach" those who are marginalized and left behind, and support the improvement of quality and competitiveness; more useful if educational technology is also capable of giving birth to generations that have personal independence. In this case is needed quality control of content and learning process pursued through the utilization of educational technology. In this case, Islamic education with the foundation of the teachings of the Qur'an, in principle has provided a high enough motivation for the people to come forward and able to become khalifah on earth, in order to achieve real prosperity. Thus, education should be truly responsive to the changes and demands of the times, especially related to the development of information-communication technology, as well as to be a strengthening of technology-based Islamic education, especially information-communication technology in order to really have great benefits for the masak world.